2016
DOI: 10.1093/bja/aew028
|View full text |Cite
|
Sign up to set email alerts
|

Extrafascial injection for interscalene brachial plexus block reduces respiratory complications compared with a conventional intrafascial injection: a randomized, controlled, double-blind trial

Abstract: NCT02074397.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 20 publications
4
34
1
1
Order By: Relevance
“…They observed an incidence of 21% hemidiaphragmatic paresis following exatrafascial injection of 20 mL of 0.5% bupivacaine with epinephrine 1:200,000 [Figure 3]. [1318] In our study, block was administered for both surgical anaesthesia and analgesia. In the same study, they also observed that respiratory function was better preserved in the extrafascial group which was concordant with our study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…They observed an incidence of 21% hemidiaphragmatic paresis following exatrafascial injection of 20 mL of 0.5% bupivacaine with epinephrine 1:200,000 [Figure 3]. [1318] In our study, block was administered for both surgical anaesthesia and analgesia. In the same study, they also observed that respiratory function was better preserved in the extrafascial group which was concordant with our study.…”
Section: Discussionmentioning
confidence: 77%
“…It has been suggested based on the anatomic characteristics that lowering of incidence can be achieved by reducing the volume of local anaesthetics[171920] or by placing the tip of the needle away from C3–5 roots. [18] The distance of 4 mm from the brachial plexus sheath has been observed to be effective. [1118] Albrecht et al .…”
Section: Discussionmentioning
confidence: 99%
“…Though well tolerated in healthy patients, patients with decreased respiratory function may experience symptomatic dyspnea or hypoxia. Various methods to avoid this adverse effect, including low-volume [10] and extra-fascial injections [11], have been attempted with limited success. Blockade of the suprascapular nerve, alone or in combination with the axillary nerve, have been suggested as an alternative means of analgesia, which could minimize the risk of phrenic nerve paresis [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PNP following BPB is associated with several factors, mainly dependent on the approach to the brachial plexus. It is 21% to 100% for interscalene BPB, [ 8 , 9 ] 28% to 67% for supraclavicular BPB, [ 10 , 11 ] and 5% to 13% for infraclavicular BPB. [ 12 , 13 ] The effect of axillary BPB on the incidence of PNP has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%